Empowering Narratives: A Feminist Critical Discourse Analysis of Essays from Magdalene (Tamaddun, 2024)
Despite the recognition of gender equality within the Indonesian legal system, there remain various instances where women have disadvantages in domains including education, employment, and political representation. This study aims to highlight actions taken by women in fostering women’s empowerment through essays by applying the framework of Feminist Critical Discourse Analysis (FCDA). This study applied qualitative method to conduct a content analysis of essays that address topics relating to women. The data included in this study were taken from the essays featured in the book “The Feminist Minds”. To determine gender-related issues and the actions taken to address them, the data was collected by reading and taking notes on the relevant passages of the essays. Following the collection of data, the analysis was carried out using the theoretical framework of FCDA. Several misconceptions regarding feminism and women-related issues, including street harassment, sexual abuse, and victim blaming, were discussed in the essays. Furthermore, the actions that must be taken to address them were also elaborated. The strategies included awareness campaigns, educational initiatives, legislative efforts, community support, and addressing negative stereotypes and attitudes. In conclusion, progress in addressing women-related issues can be achieved through collaborative efforts involving communities and affiliated organizations.